Analysis of Sentence Types in Affecting College Students’ Writing Skill - Hidayah, Barokatul; Bochari, Siska; Jamiluddin, H. (Elsya : Journal of English Language Studies, 2024)
College students are required to complete an undergraduate thesis as part of their final project. However, when addressing the issues students face with their limited vocabulary, their choice of proper grammar, and their syntactical or word class problems, etc., researchers seldom carried out a focused exploration on dominant sentence types. This study aims to identify the most dominant sentence type used by the students in their writing, determine the forms of sentences used within the dominant sentence type, and analyse the factors influencing students' writing. This research used a quantitative descriptive method with an innovative methodological approach, namely a fishbone diagram to analyse the underlying factors. 105 background proposals from 7th semester students in the English Department at Tadulako University participated in this study. A simple random sampling technique was employed, and questionnaires and document analysis were used as instruments to gather data. The data analysis results show that: (1) simple sentences made up the majority of the dominant sentence types used in students’ backgrounds; (2) nominal sentences were the second most common form of dominant sentences used by the students; and (3) there are three factors that impact students' writing, particularly regarding sentence types: internal and external factors. The implication of this research is the development of writing skills where sentence types are an essential part of writing. The results can aid students in crafting clear and coherent sentences, specifically how to structure sentences effectively to convey their ideas logically, avoiding run-on sentences or fragments that can obscure meaning.